Civil society and ICT governance: Hubs, spaces and sites for civil society engagement in ICT4G issues - Hecita, Ian Jayson R. (Animo Repository, 2006)
This paper will examine the issues which civil society is engaged with regard to ICT for governance. The paper will also discuss how civil society organization; particularly cases from the Philippines have addressed ICT for governance issues through activities, processes, and mechanisms, and advocacies. This study asserts that the role of civil society in ICT for governance can be appreciated by its ability to foster public opinion and locate policy issues. As a site for public discourse, civil society is well positioned to mobilize citizen support to promote JCT These interventions can take the form of generating public awareness about JCT, crafting JCT action plans for sustainable development, advancing good governance, and cooperating with reformers both sides of the public- private divide to enhance development outcomes. Over the past few years, civil society organizations in the Philippines were able to implement programs and projects needed to encourage the utility of JCT for good governance. However the initiatives have not been fully documented and widely circulated. There is a need to convert these cases of citizen participation and civil society engagements into knowledge products that can be used to maximize the benefits of the use of ICT to social development.